"Peasants, Farmers, and Tractor Drivers": Exploring the Power Relations between the Public Authorities and the Neo‐peasant Movement in Catalonia, Spain. (31st July 2022) - Hummel, Agata; Escribano, Paula
Abstract: This article focuses on power relations between the rural public authorities and the neo‐peasant movement in Catalonia (Spain). On the one hand, the public authorities promote a productivism‐oriented, professional model of farming informed by the Common Agricultural Policy. This policy results in the gradual disappearance of small‐scale agriculture. On the other hand, the neo‐peasant movement resists the productivist model of agriculture, proposing a new reinvented peasant model. We focus on how the discourses—images and labels—associated with these different models of agriculture are reproduced, perpetuated, and internalized by the different actors who use them to exercise power or resistance. More specifically, we analyze how the use of the concept of "professional farmer" is constructed as a new subjectivity and acts to exclude the peasant model of agriculture. We also explore how the concept of the "peasant" is used to resist this process of exclusion.